A signalling theory of law enforcement hiring. (4th July 2017) - Hilal, Susan; Densley, James A.; Jones, David Squier
ABSTRACT: Using qualitative interviews with 31 police chiefs, the present study explores the police hiring process in Minnesota. This is the only US state that mandates law enforcement candidates earn at least a two-year degree from a regionally accredited college or university and successfully complete a programme of professional police officer education before being hired. This system creates a large pool of ostensibly identical licence-eligible candidates, hence this article examines how hiring managers separate the high quality ones from their low quality counterparts, including methods of screening and, eventually, selecting them. Through the novel application of signalling theory, it demonstrates how the quality of any given licence-eligible police officer is assessed by evaluating observable signs of him or her that chiefs believe to be correlated with unobservable trust-warranting properties, such as honesty, loyalty, and cultural competency. Quotes from the chiefs are employed throughout the article to illustrate these themes. Implications for research, policy and practice are discussed.